GH4096 superalloy high-temperature oxidation and corrosion behaviors - Amin Wang; Jingjie Dai; Rui Fu; Hongxia Zhang; Caixia Sun; Dan Li (Journal of Materials Research and Technology)
To evaluate the stability and adaptability in complex marine environments, high-temperature oxidation, hot corrosion with NaCl–Na2SO4 deposits, and high-low temperature alternating corrosion behaviors of GH4096 superalloy were investigated in this work, along with the microstructure evolution and corrosion kinetics. The results showed that during the high-temperature oxidation and hot corrosion process, significant outward diffusion of Cr and Ti occurred. The superalloy exhibited excellent oxidation resistance at 650 °C and 750 °C, as well as good hot corrosion resistance with 5 wt% NaCl +95 wt%Na2SO4 deposits at 650 °C. The superalloy also demonstrated poor resistance to high-low temperature alternating corrosion at room temperature (RT)/650 °C, RT/750 °C, and RT/850 °C.